Muscle Architecture Adaptations to Static Stretching Training: A Systematic Review with Meta-Analysis - Ioli Panidi; Olyvia Donti; Andreas Konrad; Petros C. Dinas; Gerasimos Terzis; Athanasios Mouratidis; Vasiliki Gaspari; Anastasia Donti; Gregory C. Bogdanis (SpringerOpen, 2023)
Abstract Background Long-term stretching of human skeletal muscles increases joint range of motion through altered stretch perception and decreased resistance to stretch. There is also some evidence that stretching induces changes in muscle morphology. However, research is limited and inconclusive. Objective To examine the effect of static stretching training on muscle architecture (i.e., fascicle length and fascicle angle, muscle thickness and cross-sectional area) in healthy participants. Design Systematic review and meta-analysis. Methods PubMed Central, Web of Science, Scopus, and SPORTDiscus were searched. Randomized controlled trials and controlled trials without randomization were included. No restrictions on language or date of publication were applied. Risk of bias was assessed using Cochrane RoB2 and ROBINS-I tools. Subgroup analyses and random-effects meta-regressions were also performed using total stretching volume and intensity as covariates. Quality of evidence was determined by GRADE analysis. Results From the 2946 records retrieved, 19 studies were included in the systematic review and meta-analysis (n = 467 participants). Risk of bias was low in 83.9% of all criteria. Confidence in cumulative evidence was high. Stretching training induces trivial increases in fascicle length at rest (SMD = 0.17; 95% CI 0.01-0.33; p = 0.042) and small increases in fascicle length during stretching (SMD = 0.39; 95% CI 0.05 to 0.74; p = 0.026). No increases were observed in fascicle angle or muscle thickness (p = 0.30 and p = 0.18, respectively). Subgroup analyses showed that fascicle length increased when high stretching volumes were used (p < 0.004), while no changes were found for low stretching volumes (p = 0.60; subgroup difference: p = 0.025). High stretching intensities induced fascicle length increases (p < 0.006), while low stretching intensities did not have an effect (p = 0.72; subgroup difference: p = 0.042). Also, high intensity stretching resulted in increased muscle thickness (p = 0.021). Meta-regression analyses showed that longitudinal fascicle growth was positively associated with stretching volume (p < 0.02) and intensity (p < 0.04). Conclusions Static stretching training increases fascicle length at rest and during stretching in healthy participants. High, but not low, stretching volumes and intensities induce longitudinal fascicle growth, while high stretching intensities result in increased muscle thickness. Registration PROSPERO, registration number: CRD42021289884.